Analysis of Animal Accidents along the Road of Padamara-Karangcegak in Geospatial Perspective - Sakinah Fathrunnadi Shalihati; Esti Sarjanti (Universitas Muhammadiyah Surakarta, 2019)
The occurrence of animal accidents is one of the consequences of physical environmental interaction of animal in terms of their movement from one place to another and non physical environment in the form of transportation usage by human. Accidents happened to animals can affect the structure of the food chain. It would be a matter if it occurred continuously because some species of animals that were important to the ecosystem would not exist anymore. The records of the frequency of animal accident and habitat along Jalan Padamara-Karangcegak by geospatial could be used to analyze the correlation between the dominance of animal species getting the accidents and the potential width of the habitat owned along the road. Qualitative description was used as the method of the research. It was from the primary data analysis of the distribution of accident and secondary data of the land use from Google Earth of satellite image which was then processed by Geographic Information System. The results obtained during observations from April to July 2016 showed that there was a correlation between the animal habitat and the accidents happened. The animal with a wider habitat dominated the accidents occurred than animals with no extensive habitat.